New Principle Schemes of Freight Cars Bogies - Gorbunov, Mykola; Gerlici, Juraj; Kara, Sergey; Nozhenko, Olena; Chernyak, Ganna; Kravchenko, Kateryna; Lack, Tomas (Manufacturing Technology Journal, 2018)
In the article the issue of perspective running parts for freight cars of new generation is considered and additions to the outdated existing classification of bogie are developed, namely introduction of such types of suspension is suggested.The results of theoretical studies are presented by means of modeling the movement of the car in the software "Universal Mechanism" to determine the influence of the first stage of spring suspension in Barber type bogie (type 18-100 and analogues) on energy efficiency (resistance to movement) and the estimated value of the decrease in resistance to movement.A concept for a fundamentally new design of a freight car bogie for high-speed traffic has been prepared, based on fundamentally new technical solutions with elastic-dissipative bearing elements, as well as a concept for the modernization of the Barber-type bogie (type 18-100 and analogues) by introducing axle suspension on the 1520 mm gauge.
Keywords: Bogie; springsuspension; axle suspention; resistance to movement; elastic-dessipative bearing